A Study on Maintenance Management Practices for the Conservation of Heritage Museum Buildings in Malacca - Ezry, Syahmi; Abdul Rahman, Sr. Dr. Mohammad Ashraf (Progress in Engineering Application and Technology, 2022)
This study aims to determine maintenance management by heritage building management and propose maintenance management best practice criteria for three different heritage buildings. The primary purpose of this research is to produce a guide toward establishing good practices for the maintenance of three heritage buildings in the city of Melaka. This study employs qualitative and quantitative approaches to examine data and conclusions, taking into account several factors, such as the most effective maintenance strategy for each business. The necessity of having an organized maintenance system, complete with inventory and records, inspection importance, the significance of having work, and the requirement of having qualified staff and enough training. The research involved questionnaires and interviews and as well as case studies. The History Museum, the People's Museum, and the Governor’s Museum are the three buildings that have been chosen to serve as case studies for the investigation. A recommendation for the best practice of maintenance management for the conservation of heritage buildings has been developed based on the study conducted. This recommendation is now available for adoption by any heritage organization in Melaka. In conclusion, a solid practice for the maintenance of heritage buildings will assist in enhancing both the level of understanding and the level of facilitation necessary for conserving heritage buildings.